Breaking the Spell of the Male Gaze in Selected Women’s Ekphrastic Poems. - Zuhair Al-Wattar, Shaymaa (Journal of College of Education, 2019)
For centuries art and poetry have been inspiring each other and the relation between word and image constantly fascinates the poets. The literary world has given poems that tackle artwork the name: ekphrasis. Ekphrasis represents a rich hunting ground for references, allusions, and inspiration for poets. However, ekphrasis is powerfully gendered that privileged male gaze. Traditionally, the male is given the strong position as the gazer, while the woman is locked in her predetermined role that of the beautiful, silent, submissive, gazed upon. Women poets refuse to adhere to the gendered ekphrastic tradition and the under-representation of women in ekphrastic poetry. They strongly challenged the ekphrasis tradition modifying it to create a distinctive feminist ekphrasis. Their poetry changes the male-dominated ekphrsis tradition that for centuries has pervaded the Western cultures. The work of the poets Louise Bogan,Carol Ann Duffy, Rita Dove, and Margaret Atwood is an excellent example of women’s ekphrastic poetry that defies the tradition of patriarchal male gaze in an attempt to break the spell of the male gaze.